SOME OBSERVATIONS ON THE HANDSHAKE AS A CRUCIAL INDICATOR OF THE EMPATHIC AND PEACEBUILDING CULTURE - Puppel, Joanna (Scripta Neophilologica Posnaniensia, 2019)
Handshake is a very primeval human gesture which follows from the erect posture and the freeing of the upper limbs. Its evolutionary benefits for mankind are briefly discussed. It is emphasized that the free hands, the right hand in particular, have been of fundamental importance to human culture thus underlying interpersonal linkages and communication. Handshake is loaded semantically positively and in this capacity it serves in a number of important integrative functions in human social life, in particular, in peacebuilding.